STRATEGI ADAPTASI PETANI PADI LADANG TERHADAP PERUBAHAN MUSIM (SUATU STUDI PADA KOMUNITAS PETANI PADI LADANG DI KELURAHAN OESAO KECAMATAN KUPANG TIMUR KABUPATEN KUPANG) - Tefa, Salomi Lodia; Samin, Mikael; Hasan, Muhammad Husain (Universitas Nusa Cendana, 2025)
This research is motivated by climate change as a natural phenomenon which is currently starting to be felt in the Oesao area, East Kupang sub-district, Kupang regency. This has the impact of making it difficult for farmers to predict rainfall patterns, thus having an impact on the agricultural sector, especially rice planting. The objectives of this research are 1) To determine the behavior of rice farmers towards seasonal changes in Oesao Village, East Kupang District, Kupang Regency. 2) To find out how rice farmers adapt to seasonal changes in Oesao Village, East Kupang District, Kupang Regency. The research method used in this research is a qualitative descriptive analysis method. This type of research is qualitative descriptive research. Data collection was carried out by means of observation, interviews and documentation studies. The types of data in this research are primary data and secondary data. Primary data collection was obtained by collecting data in the form of answers from interviews with informants, and secondary data collection was obtained by collecting data obtained from notes available at the Oesao Village Head's office related to the research object. The analysis technique used in this research is qualitative analysis. Research Results: 1) use of superior seeds; adjust planting time; use of drilled wells. 2) There are three types of adaptation strategies used by rice farmers, namely the upland rice strategy, crop rotation and technical irrigation rice crop patterns.